Konsep Berpikir dan Berdzikir Dalam Q.S Ali-Imran Ayat 190-191 dan Implikasinya Terhadap Kecerdasan Spiritual Siswa - Alawiyah, Risa; Surahman, Cucu; Sumarna, Elan (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2025)
This study aims to explore the impact of instructional media, including visual, audio, and This article discusses the concept of thinking and dhikr contained in Q.S. Al-Imran verses 190-191, and its implications for students' spiritual intelligence. This verse emphasizes the importance of contemplating the creation of the heavens and the earth as a sign of Allah's greatness, as well as combining the activity of rational thinking with dhikr or remembrance of Allah. In the context of education, this combination is relevant to developing students' spiritual intelligence, which is the ability to understand the meaning of life, maintain a relationship with the Creator, and have wisdom in dealing with life. Through a thematic tafsir approach (tafsir maudhu'i), this article outlines how an understanding of the concepts of thinking and dhikr can strengthen students' spiritual awareness. The practical implications of this research suggest that teaching these verses in schools can help students achieve a balance between intellect and spirituality, so that they are able to think critically while having a deep sense of faith.